Integrated water operations under climate change: Uluova Micro Basin example - Sekerci, Kuersat; Tuna, Muhammed Cihat; Dogan, Mustafa Sahin (Iwa Publishing, 2024)
This study examines the impact of climate change on the Uluova Micro Basin, Turkey, employing an optimization model named ULUHEM across various water management and climate scenarios. With ULUHEM, the effects of different climate impact scenarios on agricultural water allocations, pumping costs, water scarcity, and scarcity costs were analyzed. The primary objective of this study is to identify gaps in demand within the current water supply infrastructure due to global warming and to develop adaptation strategies for basinwide water management operations. The research also emphasizes the importance of creating a basin-based hydroeconomic model that includes other surface water resources with a sustainable management approach to address the impact of climate change. In summary, the impacts of climate change on surface waters and groundwater in the Uluova Micro Basin include changes in water availability, water scarcity, and associated costs, and these have implications for agricultural water allocations and overall water management in the region. The study found that drier climate periods lead to reduced surface and groundwater input to farmland, resulting in increased water scarcity and scarcity costs. Conversely, periods characterized by wetter climates yield contrasting outcomes, alleviating water scarcity and its corresponding costs.
Keywords: basin management; climate change; ULUHEM; water resources